(untitled) (Transport systems and technologies, 2019)
In Ukraine today there is a high dynamics of container handling of export-import goods. But at the same time, the problem of unclaimed cargo in containers appears in the port: their use of storage areas, return of empty containers to a linear carrier, paperwork for the stale cargo and operations for its destruction. All this takes enough time and does not allow efficient use of storage areas and containers. The paper proposes to reduce the time for documenting such goods using the network planning method. According to the results of the calculations, it is proposed to carry out part of the operations simultaneously, which reduces the total clearance time by an insignificant number of hours, and this will amount to more than a month per year. During this time, the freight forwarding company has the opportunity to earn additional funds and save valuable time for its client line carrier, which in turn also has the opportunity to make a profit for using its equipment. At the same time, it is proposed to the freight forwarding company to join the information system of the port community. This increases the efficiency of the freight forwarder and thus saves time for the linear carrier. The results of economic calculations indicate that the use of these systems is sufficiently profitable, despite the rather small annual cargo turnover of stale cargo accepted for calculations.